Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2166/wp.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

The strategies of policy entrepreneurs in water transitions around the world

Abstract: This paper discusses sixteen instances of radical water policy change across the globe. The key question we seek to answer is about the role of individuals in such transitions. 'We call these individuals 'policy entrepreneurs' and we suggest that they can affect transitions through a set of strategies, such as idea development, coalition building, the detection and exploitation of v^^indows of opportunity, network management, and venue shopping. Our empirical analysis shows that individuals do contribute to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 29 publications
(59 reference statements)
1
81
0
1
Order By: Relevance
“…In Huitema and Meijerink (2009a), we present 11 additional country studies along with an analysis of water transitions in the European Union (EU). Together, these 16 accounts of major change in water policies provide a solid empirical basis for investigating the role of policy entrepreneurs in realizing water policy transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In Huitema and Meijerink (2009a), we present 11 additional country studies along with an analysis of water transitions in the European Union (EU). Together, these 16 accounts of major change in water policies provide a solid empirical basis for investigating the role of policy entrepreneurs in realizing water policy transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In our comparative study, we found ample evidence for the highly political nature of RBO formation and reform processes and the crucial role of change agents therein, but we also learned that the actions of these agents interact with specific events or triggers, which, in the literature, are often referred to as windows of opportunity (Kingdon 1995, Huitema andMeijerink 2009). Table 3 lists the main windows of opportunity and the actors pushing or hindering RBO formation and reform for each case study.…”
Section: Institutional Dynamics and The Politics Of River Basin Organmentioning
confidence: 79%
“…Collaborative leadership is necessary to bridge gaps, span boundaries and build coalitions between different actors and sectors. Policy entrepreneurs may provide for this type of leadership (Partzsch and Ziegler 2011;Huitema and Meijerink 2009).…”
Section: Coordination Mechanismsmentioning
confidence: 99%